A terbium(iii)-based coordination polymer for selective and sensitive sensing of nitroaromatics and ferric ion: synthesis, crystal structure and photoluminescence properties. (2nd October 2017) - Feyisa Bogale, Raji; Chen, Yanzhen; Ye, Junwei; Zhang, Siqi; Li, Yiwen; Liu, Xigang; Zheng, Ting; Rauf, Abdul; Ning, Guiling
Abstract : A Tb(iii )-based coordination polymer has been synthesized and it is a visually selective and sensitive sensor for the detection of 4-nitrophenol and Fe 3+ ion. Abstract : A potent luminescent sensor for the detection of 4-nitrophenol (4-NP) and Fe 3+ ion was developed based on a terbium(iii )-based coordination polymer, [Tb(H2 O)5 (BTEC)][H(C5 H6 N2 )]·3H2 O (1 ), which was prepared under hydrothermal condition using a benzene-1, 2, 4, 5-tetracarboxylate (BTEC) bridging ligand.1 possesses one-dimensional zig-zag chains decorated with carboxylate functional sites and protonated 4-aminopyridine guests located in interlayer channels. The strong green emission of1 could be efficiently quenched by trace amounts of 4-NP through a luminescence quenching mechanism even in the presence of other aromatic compounds such as 1, 2-dimethylbenzene, bromobenzene, phenol, 4-bromophenol, 4-nitrotoluene, 1, 2-dinitrobenzene, nitrobenzene, 2, 6-dinitrotoluene, and 2, 4, 6-trinitrophenol. Furthermore, 1 exhibits superior luminescence quenching behavior towards Fe 3+ ion over other competing interfering metallic ions such as Cr 3+, Cu 2+, Na +, Mg 2+, Mn 2+, Co 2+, Fe 2+, Pb 2+, Pd 2+, and Zn 2+ . The possible luminescence quenching mechanisms were also discussed. Moreover, visual fluorescent test papers based on1 were fabricated and could be utilized for selective detection of nitroaromatic compounds and metal ions.